The Outcome of Endonasal Endoscopic Versus Transcanalicular Laser Dacryocystorhinostomy - Khalid, Amber; Sultan , Sharjeel; Khanzada, Mahtab Alam; Muhammad wasif; Bhatty, Ayoob; Aveen fatima (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: The purpose of our research was to analyze and compare the outcome of Endonasal Endoscopic (EE-DCR) versus Endoscopic Trans-canalicular Laser assisted Dacryocystorhinostomy (TC-DCR) for the treatment of Dacryocystitis METHODOLOGY: This study was a non-randomized control trial executed by the Department of Ophthalmology in collaboration with the Otorhinolaryngology (ENT) department at Ziauddin University Hospital Karachi. The study spanned two years, from August 2021 to July 2023. All patients were selected based on inclusion criteria, presented with complaints of epiphora in the ophthalmology department, and were assessed clinically by an ophthalmologist and ENT surgeon. The data was compiled in SPSS 23, and comparative data was analyzed using a chi-square test. RESULTS: In this research, we analyzed and compared the functional and anatomical outcomes of EE-DCR versus TC-DCR. The mean age of participants was 39.4± 2.3 years in both groups. In the EE-DCR group, there were 15 men (26.3%) and 42 women (73.7%), while in the TC-DCR group, there were 13 men (22.5%) and 27 women (67.5%). The outcome for TC-DCR was successful in 90% of cases, slightly higher than 84.2% for EE-DCR. CONCLUSION: TC-DCR is considered a better surgical approach than EE-DCR because it is minimally invasive, safe and less time-consuming. The outcome of both procedures was assessed postoperatively in terms of functional and anatomical success rate, and TC-DCR showed slightly better results.